THE INFLUENCE OF ECONOMIC AND ENERGY CRISIS ON PRICE OF AGRICULTURAL PRODUCTS - Dejanović, Mirjana (Economics of Agriculture, 2023)
The purpose of this research is to explain the impact of the economic and energy crisis on the rise of prices of agricultural products and further development of a sustainable agricultural economy in Serbia. In the paper are used comparative data for analysis of the movement of agricultural production and inflation in the last 10 years. The evident result of the research is the great impact of the economic and energy crisis on the rise of prices of agricultural products and rising inflation. The main task of this research is to help to understand factors which are connected to the rise of prices of agricultural products, and to suggest adequate solutions for stopping inflation with the aim to obtain the supply of necessary foods in periods of crisis. In paper are recommended new strategies which will contribute to the proper treatment of agricultural production in the future and sustainable development.